Analisis Biaya Pemeliharaan Bangunan Gedung The Sanctoo Resort – Sanctoo Suite & Villas - Ni Made Sintya Rani (Jurnal Talenta Sipil, 2023)
The growth of tourism in Bali includes the development of infrastructure and building facilities, such as hotels and resorts. To ensure the comfort of these building facilities, regular maintenance of the buildings and facilities is necessary. The Sanctoo Resort - Sanctoo Suite & Villa is one of the resorts located in Sukawati, Gianyar, Bali. The resort conducts periodic maintenance and rehabilitation of its buildings and facilities, although the maintenance cost calculations have not been detailed. The objective of this study is to determine the Bill of Quantities (BoQ) for maintenance and rehabilitation and evaluate the feasibility of the rehabilitation BoQ. The analysis of building maintenance costs utilizes the Work Breakdown Structure (WBS) method, which involves identifying and detailing the necessary activities for maintenance work. Based on the WBS results, the BoQ for maintenance and rehabilitation is prepared, taking into account the volume of work based on observations and interviews with The Sanctoo Resort regarding the condition and types of damages to the buildings. The analysis reveals that the maintenance BoQ for The Sanctoo Resort amounts to Rp895,367,344 per year, while the rehabilitation BoQ amounts to Rp111,379,626. The percentage evaluation of the feasibility of the rehabilitation BoQ indicates a value of 0.14%, suggesting that the damages incurred are minor and the rehabilitation budget is suitable and aligned with field observations..